The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s2179-64912012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Satisfação de idosos com os aparelhos de amplificação sonora individual nos primeiros seis meses de uso

Abstract: OBJETIVO: Analisar a satisfação do idoso usuário de amplificação após um, três e seis meses de uso do Aparelho de Amplificação Sonora Individual (AASI). MÉTODOS: Estudo longitudinal com 22 idosos que iniciaram o processo de seleção e adaptação de AASI em um serviço de alta complexidade. A pesquisa foi realizada no dia da adaptação dos AASI e nos retornos de um, três e seis meses do paciente à instituição e constou na aplicação do questionário Satisfaction With Amplification in Daily Life (SADL). Para avaliar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
2
0
6
Order By: Relevance
“…It was observed, in the present research, that there was reluctance in expressing negative opinion or criticism, perhaps because some individuals are afraid of losing the right to be received at the clinic or the HA use. It was also observed in another study 8,9 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It was observed, in the present research, that there was reluctance in expressing negative opinion or criticism, perhaps because some individuals are afraid of losing the right to be received at the clinic or the HA use. It was also observed in another study 8,9 .…”
Section: Discussionsupporting
confidence: 76%
“…In another research, it was also observed that the positive effect increased after the first three months of use. It means that three months of HA use were enough to increase the score of positive effects and this result remained after six months 8 .…”
Section: And 52)mentioning
confidence: 95%
See 1 more Smart Citation
“…Com relação ao local de origem, a maior concentração de estudos derivou da região Sudeste (41,7%), seguida, respectivamente, pelas regiões Sul (29,1%), Norte (16,7%) e Nordeste (12,5%). O estado de São Paulo reuniu a maioria das publicações (17)(18)(19)(20)(21)(22)(23)(24) , junto a Rio Grande do Sul (25)(26)(27)(28)(29) , Rondônia (30)(31)(32) e Minas Gerais (33,34) . Os estados de Santa Catarina (35) , Paraná (36) , Tocantins (37) , Pernambuco (38) , Bahia (39) e Paraíba (40) apresentaram apenas 1 artigo cada.…”
Section: Resultsunclassified
“…A totalidade de publicações inseridas utilizou questionários de autoavaliação como recursos para avaliar a satisfação dos usuários. O questionário Satisfaction with Amplification in Daily Life (SADL) foi aplicado em 54,2% das pesquisas (19,20,22,23,25,27,29,31,32,(35)(36)(37)39) , enquanto que os questionários International Outcome Inventory for Hearing Aids (IOI-HA) (17,18,21,24,26,28,30,34,38,40) e Avaliação do Serviço de Saúde Auditiva e Uso do Aparelho de Amplificação Sonora Individual (33) foram utilizados em 41,7% e 4,1% dos estudos, respectivamente.…”
Section: Resultsunclassified